The Prayer-Book Roots of Griffith Jones's Evangelism*. (1st June 2020) - Harding, John
This article discusses Griffith Jones (1683–1761) an influential Church of England rector in West Wales from 1711, who is usually described as a precursor of Welsh Methodism and Evangelicalism. It refers to an undated, damaged notebook, in the National Library of Wales, containing sermon notes in Jones's own hand. The article seeks to trace the source of his evangelistic outlook, noting his conformist loyalty to the Church of England's doctrine, order and worship. Contrary to the opinion which attributes his pursuit of evangelism, with its seeking of conversions, to supposed Puritan influences, the article shows that the Book of Common Prayer was its inspiration. Preaching is discussed as the predominant component of worship. Jones's thought as a popular evangelist is examined, with reference to the brief sermon outlines in Welsh. The article discusses Jones's view of the defiance of Christian standards and ignorance of the faith, in Wales. Jones's practice was to summon people to faith. He preached this to those within the 'visible' national Church, which included infants, adding a strong demand for moral conformity. His concept of 'membership' was not postEnlightenment voluntarism, but of a statutory and biblical duty. For Griffith Jones the liturgy was not a disincentive to piety, contrary to some Dissenters' misgivings. His wish was for spiritual and moral renewal, not further reformation of Anglican doctrine or practice. He saw catechizing as a means against schismatical vagaries. His famous Circulating Schools reinforced this policy.